KH. M. Ishomudin Hadziq Contribution to the Islamic Education Development at Pesantren Tebuireng: the Codification of KH. Hasyim Asy'ari's Thoughts - Rohmah, Ni'matur; Hanifuddin (International Journal of Islamic Thought and Humanities, 2024)
This study explores the intellectual contribution of KH. Muhammad Ishomuddin Hadziq (Gus Ishom) in revitalising Islamic education at Pesantren Tebuireng through codifying literary works by KH. Hasyim Asy'ari. The research was driven by the academic neglect of these manuscripts, many of which were no longer taught at the pesantren since 1946. This study employs a qualitative historical method, combining document analysis, literature study, and in-depth interviews with family members and pesantren figures. The findings reveal that Gus Ishom systematically collected, verified, and published several of his grandfather's manuscripts—such as Adab al-'Ālim wa al-Muta'allim, al-Tibyān, and Risālah Ahl al-Sunnah wa al-Jamā'ah—into the compilation Irsyādus Sārī. These efforts restored Tebuireng's intellectual legacy and reintroduced classical Islamic thought into the formal curriculum of Pesantrens and Islamic universities. This codification contributed to the reintegration of traditional Pesantren scholarship (turāth) into modern Islamic education, while establishing a model for contextualising classical texts. The study concludes that Gus Ishom's scholarly initiative had a transformative impact on the development of Islamic education and the intellectual identity of Pesantren Tebuireng.